The anti-leukemic activity of sodium dichloroacetate in p53mutated/null cells is mediated by a p53-independent ILF3/p21 pathway. - Agnoletto, Chiara; Brunelli, Laura; Melloni, Elisabetta; Pastorelli, Roberta; Casciano, Fabio; Rimondi, Erika; Rigolin, Gian Matteo; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2015)
B-chronic lymphocytic leukemia (B-CLL) patients harboring p53 mutations are invariably refractory to therapies based on purine analogues and have limited treatment options and poor survival. Having recently demonstrated that the mitochondria-targeting small molecule sodium dichloroacetate (DCA) exhibits anti-leukemic activity in p53wild-type B-CLL cells, the aim of this study was to evaluate the effect of DCA in p53mutated B-CLL cells and in p53mutated/null leukemic cell lines. DCA exhibited comparable cytotoxicity in p53wild-type and p53mutated B-CLL patient cell cultures, as well as in p53mutated B leukemic cell lines (MAVER, MEC-1, MEC-2). At the molecular level, DCA promoted the transcriptional induction of p21 in all leukemic cell types investigated, including p53null HL-60. By using a proteomic approach, we demonstrated that DCA up-regulated the ILF3 transcription factor, which is a known regulator of p21 expression. The role of the ILF3/p21 axis in mediating the DCA anti-leukemic activity was underscored by knocking-down experiments. Indeed, transfection with ILF3 and p21 siRNAs significantly decreased both the DCA-induced p21 expression and the DCA-mediated cytotoxicity. Taken together, our results emphasize that DCA is a small molecule that merits further evaluation as a therapeutic agent also for p53mutated leukemic cells, by acting through the induction of a p53-independent pathway.

The p53 transcriptional pathway is preserved in ATMmutated and NOTCH1mutated chronic lymphocytic leukemias. - Athanasakis, Emmanouil; Melloni, Elisabetta; Rigolin, Gian Matteo; Agnoletto, Chiara; Voltan, Rebecca; Vozzi, Diego; Piscianz, Elisa; Segat, Ludovica; dal Monego, Simeone; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
By using next generation sequencing, we have analyzed 108 B chronic lymphocytic leukemia (B-CLL) patients. Among genes involved in the TP53 pathway, we found frequent mutations in ATM (n=18), TP53 (n=10) and NOTCH1 (n=10) genes, rare mutations of NOTCH2 (n=2) and CDKN1A/p21 (n=1) and no mutations in BAX, MDM2, TNFRSF10A and TNFRSF10B genes. The in vitro treatment of primary B-CLL cells with the activator of p53 Nutlin-3 induced the transcription of p53 target genes, without significant differences between the B-CLL without mutations and those harboring either ATM or NOTCH1mutations. On the other hand, the subgroup of TP53mutated B-CLL exhibited a significantly lower induction of the p53 target genes in response to Nutlin-3 as compared to the other B-CLL samples. However, among the TP53mutated B-CLL, those showing mutations in the high hot spot region of the DNA binding domain [273-280 aa] maintained a significantly higher p53-dependent transcriptional activity as compared to the other TP53mutated B-CLL samples. Since the ability to elicit a p53-dependent transcriptional activity in vitro has a positive prognostic significance, our data suggest that ATMmutated, NOTCH1mutated and surprisingly, also a subset of TP53mutated B-CLL patients might benefit from therapeutic combinations including small molecule activator of the p53 pathway.
Keywords: Aged; Aged, 80 and over; Ataxia Telangiectasia Mutated Proteins; Base Sequence; Female; Genes, p53; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Models, Molecular; Molecular Sequence Data; Mutation; Receptor, Notch1; Signal Transduction; Tumor Suppressor Protein p53

Sodium dichloroacetate exhibits anti-leukemic activity in B-chronic lymphocytic leukemia (B-CLL) and synergizes with the p53 activator Nutlin-3. - Agnoletto, Chiara; Melloni, Elisabetta; Casciano, Fabio; Rigolin, Gian Matteo; Rimondi, Erika; Celeghini, Claudio; Brunelli, Laura; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
The anti-leukemic activity of the mitochondria-targeting small molecule sodium dichloroacetate (DCA), used alone and in association with the small molecule inhibitor of the p53/MDM2 interaction Nutlin-3, was analyzed in primary B-chronic lymphocytic leukemia (B-CLL) samples (n=22), normal peripheral blood cells (n=10) and in p53wild-type EHEB, JVM-2, JVM-3 B lymphoblastoid cell lines. DCA exhibited a dose-dependent anti-leukemic activity in both primary B-CLL and B leukemic cell lines with a functional p53 status and showed a synergistic cytotoxic activity when used in combination with Nutlin-3. At the molecular level, DCA positively regulated p53 activity, as documented by post-transcriptional modifications of p53 protein and synergized with Nutlin-3 in increasing the expression of the p53-target genes MDM2, PUMA, TIGAR and in particular p21. The potential role of p21 in mediating the DCA+Nutlin-3 anti-leukemic activity was underscored in knocking-down experiments. Indeed, transfection of leukemic cells with p21 siRNAs significantly decreased the DCA+Nutlin-3-induced cytotoxicity. Taken together, our data emphasize that DCA is a molecule that merits to be further evaluated as a chemotherapeutic agent for B-CLL, likely in combination with other therapeutic compounds.
Keywords: Aged; Aged, 80 and over; Dichloroacetic Acid; Drug Synergism; Female; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Middle Aged; Piperazines; Tumor Suppressor Protein p53

Simian virus 40 efficiently infects human T lymphocytes and extends their lifespan. - Mazzoni, Elisa; Rigolin, Gian Matteo; Alaribe, Franca Nneka; Pancaldi, Cecilia; Maniero, Stefania; Comar, Manola; Martini, Fernanda; Tognon, Mauro (Exp Hematol, 2012)
The relevance of viral infections to the onset and progression of human hematologic malignancies and other blood diseases is still a matter of active investigation. Purified human T lymphocytes isolated from the peripheral blood mononuclear cells of healthy blood donors were experimentally infected with simian virus 40 (SV40), a small DNA tumor virus. SV40-positive T lymphocytes extended their lifespan up to day 80 postinfection (PI). Expression of viral antigens, such as the large T antigen and the viral capsid protein VP1 from the early and late regions, respectively, was detected up to day 40 PI. SV40 viral progeny were continuously produced from day 10 to 40 PI. SV40 DNA sequences were detected in infected T cells for up to 80 days. Our data indicate that human T lymphocytes can be efficiently infected with SV40. Although T cells infected by SV40 were not immortalized, 30% of these lymphocytes appeared to be morphologically transformed with an enlarged T-cell shape. Our investigation provides a simple model for studying the interactions of human T lymphocytes with this small DNA tumor virus and it might represent an experimental tool for investigating new biomarkers and targets for innovative therapeutic approaches.
Keywords: Antigens, Polyomavirus Transforming; Cell Line, Transformed; Cell Survival; Humans; Microscopy, Electron, Transmission; Simian virus 40; T-Lymphocytes

Dasatinib plus Nutlin-3 shows synergistic antileukemic activity in both p53 wild-type and p53 mutated B chronic lymphocytic leukemias by inhibiting the Akt pathway. - Zauli, Giorgio; Voltan, Rebecca; Bosco, Raffaella; Melloni, Elisabetta; Marmiroli, Sandra; Rigolin, Gian Matteo; Cuneo, Antonio; Secchiero, Paola (Clin Cancer Res, 2011)
PURPOSE: To analyze the effect of the combination of Dasatinib, a multikinase inhibitor, plus Nutlin-3, a nongenotoxic activator of the p53 pathway, in primary B chronic lymphocytic leukemia (B-CLL) patient samples and B leukemic cell line models. EXPERIMENTAL DESIGN: The induction of cytotoxicity was evaluated in both primary B-CLL cell samples (n = 20) and in p53(wild-type) (EHEB, JVM-2) and p53(deleted/mutated) (MEC-2, BJAB) B leukemic cell lines. The role of Akt in modulating leukemic cell survival/apoptosis in response to Dasatinib or Dasatinib + Nutlin-3 was documented by functional experiments carried out using specific pharmacological inhibitors and by overexpression of membrane-targeted constitutively active form of Akt. RESULTS: The combination of Dasatinib + Nutlin-3 exhibited a synergistic cytotoxicity in the majority (19 out of 20) of B-CLL samples, including patients carrying 17p- (n = 4), and in both p53(wild-type) and p53(deleted/mutated) B leukemic cell lines. At the molecular level, Dasatinib significantly counteracted the Nutlin-3-mediated induction of the p53 transcriptional targets MDM2 and p21 observed in p53(wild-type) leukemic cells. Conversely, Nutlin-3 did not interfere with the ability of Dasatinib to decrease the phosphorylation levels of ERK1/2, p38/MAPK, and Akt in both p53(wild-type) and p53(deleted/mutated) B leukemic cell lines. A critical role of Akt downregulation in mediating the antileukemic activity of Dasatinib and Dasatinib + Nutlin-3 was demonstrated in experiments carried out by specifically modulating the Akt pathway. CONCLUSIONS: These findings suggest that Dasatinib + Nutlin-3 might represent an innovative therapeutic combination for both p53(wild-type) and p53(deleted/mutated) B-CLL.
Keywords: Antineoplastic Agents; Apoptosis; Cell Line, Tumor; Cell Survival; Down-Regulation; Drug Synergism; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Mutation; Piperazines; Protein Kinase Inhibitors; Protein Kinases; Proto-Oncogene Proteins c-akt; Pyrimidines; Thiazoles; Transcription, Genetic; Tumor Suppressor Protein p53